1997
DOI: 10.1155/tsm.32.107
|View full text |Cite
|
Sign up to set email alerts
|

Texture in Metallic and CeramicFilms and Coatings

Abstract: The properties of films and coatings can be optimized for a variety of applications by modifying their texture. Understanding how the texture in thin films is formed and how it can be controlled during film growth process is one of the most important areas of texture research. Several examples were selected to illustrate how the texture in films and coatings is developed and to explain how various properties of films are affected by texture. In particular, texture development during electrodeposition of Zn-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Nevertheless, preferred orientations in electrodeposited ternary Fe-Cr-Ni alloys remain less investigated. Previously, it was repeatedly shown that even low concentrations of additional metal ions in the electrolyte can cause drastic changes of crystal orientations in electrodeposited metallic materials, (see, e.g., works [20,21]). Therefore, the investigations of joint influence of nickel and chromium on preferred orientations in iron-based coatings seem to be of sufficient scientific interest.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, preferred orientations in electrodeposited ternary Fe-Cr-Ni alloys remain less investigated. Previously, it was repeatedly shown that even low concentrations of additional metal ions in the electrolyte can cause drastic changes of crystal orientations in electrodeposited metallic materials, (see, e.g., works [20,21]). Therefore, the investigations of joint influence of nickel and chromium on preferred orientations in iron-based coatings seem to be of sufficient scientific interest.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental Verification of Selective Growth by Temperature Gradient Annealing [15,16] Specimens used in our experiments were prepared by one-stage cold rolling method, using (Al,Si)N as a grain growth inhibitor [17,18]. Selective growth of Goss grains has been verified by the direct observation of texture evolution during grain growth utilizing temperature gradient annealing.…”
Section: Introductionmentioning
confidence: 99%